Synthesis, Characterization and Biological Activities of 3,5-Diaryltetrahydro-N-[(phenylamino)methyl]-1,4-thiazine-1,1-dioxide - V. Sundari; G. Nagarajan; S. Gurumurthy; R. Valliappan (E-Journal of Chemistry)
Synthesis of 3,5-diaryltetrahydro-N- [(4’-nitroanilino)methyl-thiazine-1,1-dioxide and N-[(4’-methylanilino)methyl-]-1,4-thiazine-1,1-dioxides by condensing 3,5-diaryl-tetrahydro-1,4-thiazine-1,1-dioxide with formaldehyde and 4-nitroaniline/4-methylaniline in the presence of hydrochloric acid is reported. The structures of the synthesized compounds have been confirmed by elemental and spectral analysis. The preliminary screening of the compounds for their biological activities gives significant results